Approach Paper on the Fifth Five Year Plan [1974-79] Government of Gujarat - Planning Commission (Planning Commission, 1974)
Basic objectives of planned economic development in the country are best stated in the directive principles of the Constitution. These enjoin the State to ensure to all its citizens “the right to an adequate means of livelihood” and “to so distribute the ownership and control of material resources of the community as best to subserve the common good”. the Constitution further emphasises that the State “shall promote with special care the educational and economic interests of the weaker sections of the people and, in particular, of the Scheduled Castes and Scheduled Tribes and shall protect them from social injustice and all forms of exploitation”. Any planning exercise must therefore aim at subserving these basic objectives.
Government of Gujarat, General Administration Department (Planning)